2019
DOI: 10.1038/s41598-019-44105-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon content-tuned martensite transformation in low-alloy TRIP steels

Abstract: Ultrahigh strength and good ductility are obtained for two low-alloy transformation-induced-plasticity steels fabricated by the quenching and partitioning (Q&P) processing, respectively. Compared to 0.19 wt.% C steel in which γ → α′-martensite transformation is the dominant mechanism under deformation, the relatively high C content of austenite in 0.47 wt.% C steel is responsible for the transformation from γ to ε-martensite, suggesting that the transformation is not solely determined by the stacking fault ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…The appearance of the metastable phases named in this section as a product of SIT/DIT mainly depends on the chemical composition of the steel and on the deformation temperature. Hence, whereas the formation of stress or strain induced α is very common in many different microstructures [23,25,35,[49][50][51][52][53][54][55][56], ε is mainly found in austenitic steels [23,25,39,48,52], although it has been sporadically detected in multiphase steels [47]. The formation of α B has not been reported, to the authors' knowledge, at room temperature, although it has been found in fully austenitized steels [35] and in multiphase steels [1,3,57] deformed at high temperatures.…”
Section: Metastable Phases Formed By Stress and Strain Induced Transfmentioning
confidence: 76%
See 2 more Smart Citations
“…The appearance of the metastable phases named in this section as a product of SIT/DIT mainly depends on the chemical composition of the steel and on the deformation temperature. Hence, whereas the formation of stress or strain induced α is very common in many different microstructures [23,25,35,[49][50][51][52][53][54][55][56], ε is mainly found in austenitic steels [23,25,39,48,52], although it has been sporadically detected in multiphase steels [47]. The formation of α B has not been reported, to the authors' knowledge, at room temperature, although it has been found in fully austenitized steels [35] and in multiphase steels [1,3,57] deformed at high temperatures.…”
Section: Metastable Phases Formed By Stress and Strain Induced Transfmentioning
confidence: 76%
“…ε-martensite has been mainly studied in high manganese steels or in austenitic steels (>12 wt. %) [39][40][41][42][43][44][45][46], although it has also been observed in a low fraction in low-alloy steels [47]. Its nucleation occurs from randomly spaced overlapping γ stacking faults formed at grain boundaries [39] and, in many occasions, it is an intermediate phase during the α -martensite, i.e., the martensitic transformation follows the sequence γ→ ε →α [48].…”
Section: Metastable Phases Formed By Stress and Strain Induced Transfmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its remarkable effects on the solidification mode [ 7 , 8 , 9 ], the relative stability of austenite [ 10 ] and ferrite [ 11 ], and the M s temperature [ 12 , 13 , 14 ], carbon plays an important role in the microstructure evolution of stainless steels. The noticeable effect of carbon on the microstructure formation after welding of stainless steels, for instance, can be implied from its large coefficient in the existing empirical equations for the calculation of the Ni equivalent in Schaeffler diagrams [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…La tercera generación de aceros Q&P AHSS pretende aumentar la ductilidad conservando parcialmente una elevada resistencia mecánica [295]. Producto de su composición química (véase en tabla 1), el acero Q&P-Nb investigado presenta el mecanismo TRIP debido a la energía de falla por apilamiento (SFE por sus siglas en inglés) característica de este refuerzo (véase la Figura 16.A).…”
Section: Análisis Mecánicounclassified